PENILAIAN KONDISI MENGGUNAKAN METODE HEMISPHERICAL PHOTOGRAPHY PADA EKOSISTEM MANGROVE DI PESISIR DESA MINALULI, KECAMATAN MANGOLI UTARA. KABUPATEN KEPULAUAN SULA, PROVINSI MALUKU UTARA - Abdurrachman Baksir; Mutmainnah Mutmainnah; Nebuchadnezzar Akbar; Firdaut Ismail (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2018)
Minaluli Village has the availability of mangrove ecosystem resources in coastal areas. The availability of evenly distributed mangrove ecosystems can have a direct impact on the community. Determination of mangrove status conducted previously using conventional methods such as transect quandrat and spot check. Hemispherical photography method is one of the new methods used and developed in Indonesia. The study was conducted in July 2018 in Minaluli Village, North Mangoli District, Sula Islands Regency. North Maluku Province. The research objective is to obtain information on the condition of the mangrove ecosystem using the Hemispherical photography method. The results of the study obtained measurements of environmental parameters showed that environmental ecological conditions support the existence of mangroves. Morphological identification was obtained as many as 8 species from 3 families. Station I found 82% mangrove cover presentation value, for station II found 77% cover presentation, at station III found a presentation found 78% while at station IV found a presentation of mangrove cover 72%. The total presentation of mangrove cover obtained in the solid category, based on the standard criteria for mangrove damage. The density of the mangrove ecosystem obtained shows high density at each station. Based on the standard criteria for damage, the density of mangroves in this location is in the medium to very dense category with a value range between 1,067-2,022 trees / ha. Important value index (INP) analysis of each type of mangrove found a range of values ​​between 31.73-95.55 The highest value index of the highest species was found in the Rhizophora stylosa type with a value of 95.55% then Rhizophora apiculata with a value of 95.08%, Rhizophora mucronata namely 81.05%, Xylocarpus granatum is 45.68, Ceriops stagal with value of 40.83%, Sonneratia alba with a value of 36.27 and Bruguiera gymnorhiza 31.73%.